2019
DOI: 10.1177/0361198119846470
|View full text |Cite
|
Sign up to set email alerts
|

Transportation Asset Valuation: Pre-, Peri- and Post-Fourth Industrial Revolution

Abstract: A critical component of transportation asset management, asset valuation has been applied historically largely to provide condition-based value assessments of transportation infrastructure. There are emerging opportunities for innovations in asset valuation methodology with applications in the MAP-21/FAST performance-based era, and the Fourth Industrial Revolution (4IR). Opportunities exist to incorporate a wider range of value factors to capture multiple objectives in planning, design, and rehabilitation, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…A software package, Multi-Objective Optimization System (MOOS), was programmed to facilitate implementation of the methodologies, incorporating the concepts of value and utility theory to account for inherent risk and uncertainty associated with the decision parameters ( 19 ). Amekudzi conducted a comprehensive literature review of different valuation approaches in asset management and identified emerging opportunities for innovations in asset valuation methodologies ( 20 ). In 2016, FHWA released a report to provide guidance and describe potential challenges in incorporating asset valuation into asset management financial plans by comparing U.S. practice to that in other countries ( 7 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A software package, Multi-Objective Optimization System (MOOS), was programmed to facilitate implementation of the methodologies, incorporating the concepts of value and utility theory to account for inherent risk and uncertainty associated with the decision parameters ( 19 ). Amekudzi conducted a comprehensive literature review of different valuation approaches in asset management and identified emerging opportunities for innovations in asset valuation methodologies ( 20 ). In 2016, FHWA released a report to provide guidance and describe potential challenges in incorporating asset valuation into asset management financial plans by comparing U.S. practice to that in other countries ( 7 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Infrastructures 2023, 8, 118 2 of 12 can be adjusted using either the "Depreciation" or "Modified" approach [3,11,12]. The former adjusts the cost according to a linear or curvilinear function predefined for the asset's service life, while the latter adjusts it based on the asset's current condition.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are widely utilized by transportation agencies at the local and state levels worldwide to fulfill management and financial requirements [1,2]. The "Modified" approach is particularly advantageous for management purposes as it considers the asset's condition during valuation [3,11,12]. Examples of specific methods within this approach are the Net Salvage Value (NSV), Written-Down Replacement Cost (WDRC) and Adjusted Value with Respect to Condition Threshold (AVRCT) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US transportation system, federal funding is generally distributed based on the overall asset valuation of the state/regional agency ( 10 ). The valuation framework currently being followed only looks at the condition-based value of the asset ( 11 ). This undervalues the assets with adaptive capacity and favors investment in non-adaptive assets to avoid added costs.…”
mentioning
confidence: 99%